2020
DOI: 10.1136/bmjinnov-2020-000422
|View full text |Cite
|
Sign up to set email alerts
|

Using a pharmacist-led mHealth to improve patient’s adherence of antidepressants: patients’ experiences in low resourceful country

Abstract: Depression is considered fourth leading cause of disability and premature death in the world. It is estimated that in developing countries about 25 individuals among hundred suffers from some mental disease in any part of their life. Adherence is a major factor in the success of the treatment of depression. Patients with psychiatric illness are highly affected by non-adherence. 68% of patients with depression discontinue antidepressants within 3 months of therapy initiation, whereas those patients who continue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…In Pakistan, which is a low-to middle-income country, the role of the pharmacist is still evolving, and very few studies have been evaluated the pharmacists' role in the country [17]. Our study has shown that the use of a multidisciplinary approach especially utilizing pharmacists during such limitations has proved to be highly beneficial for judicial use of expensive medication.…”
Section: Discussionmentioning
confidence: 82%
“…In Pakistan, which is a low-to middle-income country, the role of the pharmacist is still evolving, and very few studies have been evaluated the pharmacists' role in the country [17]. Our study has shown that the use of a multidisciplinary approach especially utilizing pharmacists during such limitations has proved to be highly beneficial for judicial use of expensive medication.…”
Section: Discussionmentioning
confidence: 82%
“…The role of pharmacists in Pakistan has been developing over the years. 22 In our study, all medications were prepared as per the protocol under the sterile area with medication labels which may have contributed to the high acceptance of nurses. The implementation of RTA syringes within a health system improves care, efficiency and patient safety and reduces cost.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the country's poor financial, economic, and environmental conditions, health issues in Pakistan are on the rise every day, and treatment options are limited [1]. The main cause of poor health conditions is the poverty.…”
Section: Introductionmentioning
confidence: 99%